CHARACTER-BASED LEADERSHIP IN STRENGTHENING ORGANIZATIONAL PERFORMANCE: EVIDENCE FROM A BUSINESS AND PARTNERSHIP BUREAU - Alfianty, Resya; Bimantoro, Kayla Luna; Adha, Maulana Amirul; Ansar, Rudy (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
Leadership plays a crucial role in determining organizational success, particularly in fostering a supportive and productive work environment. This study aims to analyze the implementation of character-based leadership in enhancing organizational performance within the Business and Partnership Bureau of the Student Executive Board. This research employs a qualitative descriptive approach to explore leadership practices in context. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, display, and conclusion drawing. The findings reveal that character-based leadership, reflected in openness, motivation, appreciation, communication, and humility, contributes to a collaborative and supportive work environment. These practices enhance member engagement, creativity, and organizational performance, as shown by successful program implementation and business outcomes. This study provides empirical evidence on the importance of character-based leadership in improving student organization performance.